In another world, my sister stole my name. 1 - Kotoko (Yen Press, 2024)
Through a handheld mirror connected to another world, college student Ichika shares a friendship with a boy named Cecil--one that only her older sister, Karen, knows about. When Karen and the mirror disappear one day, Ichika is devastated. But grief turns to shock a year later when she, too, is sent to the world on the other side, only to find her lost sister and a grown-up Cecil! Except...why are her sister's first words to her "I've missed you, Karen"? And why is everyone calling her "Ichika"?